2020
DOI: 10.3390/min10100910
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the Cooling Regime on the Mineralogy and Reactivity of Belite-Sulfoaluminate Clinkers

Abstract: This study investigated the influence of different cooling regimes on the microstructure and consequent reactivity of belite-sulfoaluminate clinkers. The cement clinkers were synthesized by incorporating secondary raw materials, such as titanogypsum and bottom ash, to the natural raw materials. Clinker phases were determined by Rietveld quantitative phase analysis, while the distribution morphology and the incorporation of substitute ions in the phases were characterized by scanning electron microscopy using e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 35 publications
0
10
0
Order By: Relevance
“…Moreover, a much higher amount of aphthitalite precipitated at 60 • C compared to at 40 • C, indicating that with increasing temperature above ambient, the formation of aphthitalite is increased due to a higher release of alkalis from the clinker phases. Apart from alkali sulfates present in the clinkers, the alkalis, which are incorporated in the main clinker phases, mainly in calcium sulfoaluminate [37], could be released through the dissolution of these phases [37,59] as well, reacting with sulfate from the gypsum, and form the alkali sulfate phase aphthitalite. Namely, another alkali sulfate phase thenardite (Na 2 SO 4 ) was found forming in calcium sulfoaluminate cements at high alkalinity, explained as a product of excess alkalis initially reacting with anhydrite, which retards calcium sulfoaluminate hydration and ettringite formation [60].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, a much higher amount of aphthitalite precipitated at 60 • C compared to at 40 • C, indicating that with increasing temperature above ambient, the formation of aphthitalite is increased due to a higher release of alkalis from the clinker phases. Apart from alkali sulfates present in the clinkers, the alkalis, which are incorporated in the main clinker phases, mainly in calcium sulfoaluminate [37], could be released through the dissolution of these phases [37,59] as well, reacting with sulfate from the gypsum, and form the alkali sulfate phase aphthitalite. Namely, another alkali sulfate phase thenardite (Na 2 SO 4 ) was found forming in calcium sulfoaluminate cements at high alkalinity, explained as a product of excess alkalis initially reacting with anhydrite, which retards calcium sulfoaluminate hydration and ettringite formation [60].…”
Section: Discussionmentioning
confidence: 99%
“…%). The chemical composition of the raw meal used has been described by Dolenec et al [37], while the chemical composition of the raw materials and the proportions were presented in the study by Borštnar et al [24] The phase composition of the clinker, obtained by Rietveld refinement, is given in Table 1, where the amount of calcium sulfoaluminate is the sum of the orthorhombic and cubic polymorph, and the amount of belite is the sum of β-belite and γ-belite. Raw materials were first ground and sieved through a 200 µm mesh and then homogenized.…”
Section: Methodsmentioning
confidence: 99%
“…For instance, fly ash can be used as a source of carbon for the synthesis of nanomaterials (carbon nanotubes), aerogels, geopolymers and rare earth elements [12]. Bottom ash showed better capability to be used for geotechnical construction like in roadways, embankments and fill material [13], as constituent in belite-sulfoaluminate clinkers [14] and as micro filer in concrete [15], but also as constituent in Portland cement [16] glass-ceramics [17], ceramics [18], etc. According to European Coal Combustion Products Association [19] most of the coal combustion products (CCPs) produced are used in the construction industry, in civil engineering and as construction materials in underground mining (52.4 wt.%) or for restoration of open cast mines, quarries and pits (35.9 wt.%), fly ash (FA) in blended cements (11%) and cement raw material (26%) of 21 million tons and bottom ash (BA) in cements (10%) of 2.6 million tons.…”
Section: Introductionmentioning
confidence: 99%
“…Mayenite was present in all samples regardless of the amount of fluoride added. It has been found that, in CSA clinkers, a fast cooling rate can lead to mayenite formation, which could explain the formation of mayenite even without the presence of fluoride (x 0, series 1) (Dolenec et al, 2020). Another explanation might be the substitution of Fe or Si with Al, but this is out of the scope of the title study.…”
Section: Additional Discussionmentioning
confidence: 87%